2017
DOI: 10.3389/fnhum.2017.00131
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Voluntary Self-regulation Learned through Real-Time fMRI Neurofeedback

Abstract: Neurofeedback based on real-time functional magnetic resonance imaging (fMRI) is an emerging technique that allows for learning voluntary control over brain activity. Such brain training has been shown to cause specific behavioral or cognitive enhancements, and even therapeutic effects in neurological and psychiatric patient populations. However, for clinical applications it is important to know if learned self-regulation can be maintained over longer periods of time and whether it transfers to situations with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 44 publications
6
32
1
Order By: Relevance
“…These findings are in line with previous studies evaluating transfer and maintenance effects of rt-fMRI NF-assisted control over regional brain activity [31, 75], and additionally suggest that successful neuromodulatory control on the pathway level can last beyond the duration of the initial training and thus transfer to contexts outside of the MRI environment. However, despite maintenance of the neural training success, attenuation of anxiety levels following the training of the target pathway as observed on day 1 was not maintained over the follow-up period [for similar results, see 31].…”
Section: Discussionsupporting
confidence: 80%
“…These findings are in line with previous studies evaluating transfer and maintenance effects of rt-fMRI NF-assisted control over regional brain activity [31, 75], and additionally suggest that successful neuromodulatory control on the pathway level can last beyond the duration of the initial training and thus transfer to contexts outside of the MRI environment. However, despite maintenance of the neural training success, attenuation of anxiety levels following the training of the target pathway as observed on day 1 was not maintained over the follow-up period [for similar results, see 31].…”
Section: Discussionsupporting
confidence: 80%
“…Of particular relevance for the application of NF-training approaches in clinical practice (30,60,61), the present study observed that subjects were able to maintain the control over the emotion regulation pathway and its effect on anxiety decrease in the absence of feedback and for a period of at least three days. These findings are in line with previous studies evaluating transfer and maintenance effects of rt-fMRI NF-assisted control over regional brain activity (31,62), and additionally suggest that successful neuro-modulatory control on the pathway-level can last beyond the duration of the initial training and thus transfer to contexts outside of the MRI-environment.…”
Section: Discussionsupporting
confidence: 91%
“…This continued improvement after neurofeedback training has been demonstrated in as little time as 1 day (Harmelech et al, 2013). Ability to regulate neural activity in a transfer task after rt-fMRI neurofeedback has been demonstrated to be maintained as long as 14 months (Robineau et al, 2017). Despite this, only 41 of the published studies collected and reported follow-up data (see Figure 8B for the distribution of time to follow up for these studies).…”
Section: Discussionmentioning
confidence: 99%